Beneath the Bell Jar: Exploring Esther Greenwood's Mental Health Journey in Sylvia Plath's Seminal Novel - Posumah, Jennie; Ali, Muhammad Ilham; Andries, Fivy A. (English Education Department, 2024)
This study delves into Sylvia Plath's